The emerging era of Big Data Analytics. Issue 1 (December 2016) - Hussain, Amir; Roy, Asim
Abstract We would like to welcome you toBig Data Analytics, a pioneering multi-disciplinary open access and peer-reviewed journal, which welcomes cutting-edge articles describing biologically-inspired computational, theoretical, experimental, and integrative accounts of all aspects of big data science analytics. This editorial outlines the aims, scope, and future vision of the journal.